Developing effective optimized machine learning approaches for settlement prediction of shallow foundation - Mohammad Khajehzadeh; Suraparb Keawsawasvong; Viroon Kamchoom‬; Chao Shi; Alimorad Khajehzadeh (Heliyon, 2024)
went from 0.9494 to 0.9290 to 0.9903, which is an increase of 4.5 % and 6 %.
Keywords: Geotechnical Engineering and Analysis; Dam Engineering and Safety; Geotechnical Engineering and Underground Structures